Case Report: Oral Cimetidine Administration Causes Drug-Induced Immune Hemolytic Anemia by Eliciting the Production of Cimetidine-Dependent Antibodies and Drug-Independent Non-specific Antibodies - Wu, Yuanjun; Wu, Yong; Ji, Yanli; Liu, Yanhui; Wu, Dongsheng; Liang, Jiajie; Guo, Ganping; Chen, Baochan (Frontiers in Medicine, 2021)
Previously, it was reported that multiple patients had hemolytic anemia associated with cimetidine administration, while only one patient who had received intravenous cimetidine was serologically diagnosed with drug-induced immune hemolytic anemia (DIIHA) caused by cimetidine-dependent antibodies. However, the ability of oral cimetidine intake to induce the production of antibodies has not been examined. In this study, we report a 44-year-old male patient in whom oral cimetidine administration resulted in cimetidine-dependent antibodies and drug-independent non-specific antibodies, leading to the development of DIIHA. Serological tests showed that the results of DAT for anti-IgG (3+) and anti-C3d (1+) were positive. The IgM and IgG cimetidine-dependent antibodies (the highest total titer reached 4096) were detected in the plasma incubated with O-type RBCs and 1 mg/mL cimetidine or the plasma incubated with cimetidine-coated RBCs. IgG-type drug-independent non-specific antibodies were detected in blood samples collected at days 13, 34, 41, and 82 post-drug intake. This is the first study to report that the oral administration of cimetidine can elicit the production of cimetidine-dependent antibodies which promote DIIHA, and also elicit the production of drug-independent non-specific antibodies which causes hemolytic anemia that does not depend on cimetidine and lasts longer.